Financial Performance Analysis of Universitas Negeri Malang Using Ratio, Vertical, and Horizontal Analyses for Fiscal Years 2023–2024 - Yanuard Putro Dwikristanto; Helena Christiansen; Margareta Asriastuti (Business Management, 2026)
This study aims to analyze the financial performance of Universitas Negeri Malang (UM), a public university operating under the State University Legal Entity (PTN-BH) system, by applying financial ratio analysis, vertical analysis, and horizontal analysis for the fiscal years 2023–2024. The analysis is based on the university’s Statement of Financial Position, Statement of Activities, and Statement of Cash Flows to evaluate liquidity, operational efficiency, liability structure, funding sources, and financial sustainability. The findings indicate that UM experienced significant improvement in its overall financial performance during 2024. The expense ratio decreased from 0.913 in 2023 to 0.810 in 2024, indicating improved operational efficiency. Liquidity remained exceptionally strong, with current, quick, and available funds ratios all exceeding 12, demonstrating the university’s excellent ability to meet short-term obligations. The debt-equity ratio remained very low at 0.028, reflecting minimal dependence on external financing and strong financial independence. Horizontal analysis revealed substantial growth in cash, total revenue, and annual surplus, while vertical analysis showed a more diversified revenue structure and stronger liquidity. Despite these positive results, the declining proportion of expenditures allocated to educational service programs and the high level of liquid assets suggest the need for more productive resource allocation. Overall, Universitas Negeri Malang demonstrates a healthy and sustainable financial condition supported by effective financial management and prudent resource utilization.